Sosiaalisen aktiivisuuden yhteys ikääntyneiden henkilöiden haluun elää 100-vuotiaaksi - Etolin, Oona (2025)
People are living longer, but we have little knowledge whether older individuals themselves want to live a long life, and what factors are associated with this. The wish to live a long life can in some ways be considered instinctive to humans. It tends to be strongest when aging individuals experience feelings of meaningfulness and have a good quality of life. Social activity and social relationships are associated with meaningfulness and a better quality of life. The aim of this study was to examine whether social activity is associated with older women’s and men’s will to live to 100 years of age. The topic is particularly relevant as the population of Finland is one of the most aged in the world. In this study we used data collected in 2017–2018 in the Active Ageing – Resilience and External Support as Modifiers of the Disablement Outcome (AGNES) study. The participants (n=982) were independently living women and men aged 75, 80, and 85, living in Jyväskylä, Finland. The will to live to 100 years was assessed with one question, the response being either ‘yes’ or ‘no’. Social activity was assessed with four questions, each having five response options: "very much (1)", "quite a lot (2)", "somewhat (3)", "a little (4)", and "not at all (5)". The responses were averaged, and the resulting variable was divided at the median into ’high’ and ’low’ social activity categories. Background variables included gender, age, self-rated health, living arrangement, grip strength, years of education, cognitive functioning, and symptoms of depression. The main method of statistical analysis was binary logistic regression. There was a statistically significant difference between genders (p<0.001) in the will to live to 100 years. Almost one-third (28%) of women and almost half (44%) of men expressed the will to live to 100 years. Most women (61%) and men (59%) were socially active, and there was no statistical difference between the genders in social activity. Social activity was not associated with the will to live to 100 among women or men. Social activity may not be a critical factor in older adults’ will to live to 100 years. Other factors, such as health-related aspects, may be more relevant. It is also possible that the variable created to measure social activity in this study does not properly describe the level of social activity. In the future, more research is needed regarding older adults’ will to live a long life, and what factors are associated with it.